TINJAUAN YURIDIS KEDUDUKAN PENGADILAN PAJAK PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 26/PUU-XXI/2023: Juridical Review Of The Position Of The Tax Court After The Decision Of The Constitutional Court Number 26/Puu-Xxi/2023 - Nabella Septiana Dewi; Ali Rido (AMICUS CURIAE, 2025)
The Constitutional Court Decision Number 26/PUU-XXI/2023 has consequences for the legal standing of the tax court. Nevertheless, it remains unclear if the decision mutatis mutandis alters the present condition and presence of the tax court. The issues addressed in this article are as follows: 1) How is the jurisdiction of the Tax Court governed by Law Number 14 of 2002 regarding the Tax Court?; and 2). What is the stance of the Tax Court following the release of Constitutional Court Decision Number 26/PUU-XXI/2023? This study is a normative legal research that utilizes both primary and secondary data sources. As per Law No. 14 of 2002, the Ministry of Finance exercises control over the tax court's organization, administration, and finances, thereby compromising its judicial independence. In accordance with Constitutional Court Decision No. 26/PUU-XXI/2023, the authority and oversight of the tax court has been shifted from the Ministry of Finance to the Supreme Court. By consolidating this transfer, the integration of counsel into a single judicial entity will enable the Tax Court to efficiently and independently carry out its duties and oversee its finances. Therefore, the Tax Court has the ability to prevent the misuse of authority.